2014
DOI: 10.1007/s10484-014-9246-9
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback for Psychiatric Disorders: A Systematic Review

Abstract: Biofeedback potentially provides non-invasive, effective psychophysiological interventions for psychiatric disorders. The encompassing purpose of this review was to establish how biofeedback interventions have been used to treat select psychiatric disorders [anxiety, autistic spectrum disorders, depression, dissociation, eating disorders, schizophrenia and psychoses] to date and provide a useful reference for consultation by clinicians and researchers planning to administer a biofeedback treatment. A systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
143
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(151 citation statements)
references
References 68 publications
1
143
0
7
Order By: Relevance
“…This technique involves sensors that allow the wearer to detect and learn to control functions that are normally autonomous. Systematic review indicates that biofeedback is not effective for treatment of PTSD [28] but appears to be effective overall for ameliorating psychiatric symptoms [32]. This is notable as psychosocial factors such as resilience have been shown to play a significant role in control of chronic pain [8486].…”
Section: Discussionmentioning
confidence: 99%
“…This technique involves sensors that allow the wearer to detect and learn to control functions that are normally autonomous. Systematic review indicates that biofeedback is not effective for treatment of PTSD [28] but appears to be effective overall for ameliorating psychiatric symptoms [32]. This is notable as psychosocial factors such as resilience have been shown to play a significant role in control of chronic pain [8486].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on biofeedback have shown that this technique is being tested as a treatment for other psychiatric conditions, such as anxiety disorders, depression, eating disorders and schizophrenia 54 . This is a method in which instrumentals are used with a focus on the processes of muscle relaxation, breathing techniques, awareness techniques and cognitive aspects, all of which result in easing the body's self-regulatory process 55 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite research showing the link with objective and subjective measures of arousal, a recent systematic review found a lack of quality evidence for the efficacy of EDA biofeedback for any mental health disorder thus far (Schoenberg & David, 2014). Only one study evaluating an EDA-based wearable device could be identified, trialing the Pip in a group of healthy participants using game-based apps following a stress induction (Dillon, Kelly, Robertson, & Robertson, 2016).…”
Section: Support For Eda Biofeedbackmentioning
confidence: 99%